2000
DOI: 10.1207/s15327914nc382_8
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Lactoferrin Exerts an Antimetastatic Effect and Enhances Production of IL-18 in the Intestinal Epithelium

Abstract: The effects of oral administration of bovine lactoferrin (bLF) and its hydrolysate on the lung colonization by colon 26 carcinoma were investigated. At doses of 100 or 300 mg/kg/day for seven successive days, bLFs demonstrated a significant inhibitory effect on experimental metastasis, which indicated effectiveness before and after tumor implantation. Oral administration of bLFs augmented CD4+, CD8+, and asialoGM1+ cells in the spleen and peripheral blood. Their cytotoxic activities against Yac-1 and colon 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 26 publications
3
85
0
1
Order By: Relevance
“…On the other hand, there was no difference in the number of neutrophils in PBL between the two groups. This increase of lymphocytes in PBL by LF is in accord with the previous finding by Kuhara et al (2000), that orally administered LF increased the number of cells in various lymphocyte subsets, including CD4 þ , CD8 þ and asialoGM1 þ cells, in the peripheral blood of tumour-bearing mice. CLNs are the most important lymph nodes in protection against oral infection (Elahi et al, 2000).…”
Section: Kinetics Of Numbers Of Pbl and Cln Cellssupporting
confidence: 92%
“…On the other hand, there was no difference in the number of neutrophils in PBL between the two groups. This increase of lymphocytes in PBL by LF is in accord with the previous finding by Kuhara et al (2000), that orally administered LF increased the number of cells in various lymphocyte subsets, including CD4 þ , CD8 þ and asialoGM1 þ cells, in the peripheral blood of tumour-bearing mice. CLNs are the most important lymph nodes in protection against oral infection (Elahi et al, 2000).…”
Section: Kinetics Of Numbers Of Pbl and Cln Cellssupporting
confidence: 92%
“…36,37) It has also been reported that oral administration of bLF to mice increased the secretion of anti-bLF IgA and IgG in the intestinal fluid but made no difference in the serum, and it is suggested that bLF could act as an immunostimulating factor of the mucosal immune system. 38) On the other hand, it has been demonstrated that a portion of bLF is transported into blood circulation through the intestine 32,33) as previously noted.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of cytokine production may be an important mechanism of action of LF resulting in protection of the integrity of the epithelial barrier, although data are equivocal. It was previously shown that oral LF administration stimulates the production of the proinflammatory interleukin-18 (IL-18) in the mucosa of the small intestine in rodents with experimental metastasis (Kuhara et al, 2000). No data are available regarding the effects of oral LF ingestion on IL-18 production in any other physiological conditions.…”
Section: Discussionmentioning
confidence: 99%